Transient Global Amnesia as the First Clinical Symptom for Malignant B-Cell Lymphoma with Central Nervous System Involvement - Atif Zafar; Ghulam Ishaq Khan; Sahrish Abdin; Muhammad Taimoor Khan (Case Reports in Neurological Medicine)
We present the case of an elderly male who was diagnosed with transient global amnesia (TGA), only to be diagnosed with B-cell lymphoma with central nervous system involvement a few weeks later. This is the first ever case reported in literature with lymphoma presenting as TGA. Literature review and pertinent points regarding high-yield imaging protocol for presumed TGA patients are discussed.